The Relationship of Products, Brands, and Promotions to Purchase Decisions for Honda Beat Motorcycles in Bengkulu City (Case Study at Nusantara Sakti Company, Bengkulu City) - By Kasdi; Rudi Hartono; Edwarman Edwarman (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This study aims to link products, brands, and promotions to purchasing decisions for Honda Beat motorcycles in Bengkulu City. The purpose of this research is to reveal facts, circumstances, phenomena, variables and circumstances that occurred during the research and present what is. Qualitative descriptive research interprets and tells data related to the current situation, attitudes and views that occur in society, contradictions of 2 or more circumstances, relationships between variables, differences between facts, influence on a condition, and others. This type of research uses descriptive qualitative research. Qualitative descriptive research is research that is included in the type of qualitative research. The results of the Spearman rank test have a strong relationship between the product and the decision to purchase a Honda Beat motorcycle at PT. Nusantara Surya Sakti Bengkulu Branch with a correlation value of 0.646. For the Spearman rank correlation value, the brand's relationship to the decision to purchase a Honda Beat motorcycle at PT. Nusantara Surya Sakti Bengkulu Branch with a correlation value of 0.707 with strong research criteria. And the Spearman rank correlation value for the relationship between promotions and purchasing decisions for Honda Beat motorcycles at PT. Nusantara Surya Sakti Bengkulu Branch with a correlation value of 0.815 with very strong assessment criteria